Crafting the ’I’: Ethical and Ontological Questions of AI’s Role in Youth Identity Development - Looti, Mohammed; Abd-alazim, Marwa (Journal of Human-Technology Relations, 2026)
Contemporary youth are navigating a significant developmental transition, moving from a context defined by social media into an era characterized by the integration of artificial intelligence (AI). This paper undertakes a philosophical and critical exploration of the ethical and ontological questions arising as AI expands its role in shaping how youth perceive themselves and their placement within the world. Using the concept of the "algorithmic mirror" as an analytical framework, we argue that AI systems function not as passive reflectors, but as active co-constructors of identity. We first operationalize this framework by examining the mechanics of reinforcement and categorization processes that distort self-perception. We then analyze deepening concerns regarding the erosion of authenticity and the rise of a hyper-performative self-exemplified through platforms such as BeReal and generative AI tools, alongside heightened ontological insecurity presented by AI companions like Replika. The paper delineates pressing ethical imperatives related to algorithmic bias, the commodification of behavioral data, and the evolving concept of cognitive self-determination. We conclude by advocating for the development of proactive, multi-layered frameworks, proposing strategies for critical digital pedagogy, ethical design principles centered on a fiduciary duty to youth, and nuanced governance structures. This endeavor is presented as a fundamental societal imperative for safeguarding autonomous identity development in an increasingly AI-saturated landscape.